Discussion of “The impact of the options backdating scandal on shareholders” and “Taxes and the backdating of stock option exercise dates” - Armstrong, Christopher S.; Larcker, David F. (Journal of Accounting and Economics, 2009)
Bernile and Jarrell provide extensive analysis regarding the impact of backdating the stock option exercise price on stock returns for a sample of firms identified by the Wall Street Journal. Dhaliwal, Erickson, and Heitzman investigate whether executives backdate the exercise date to obtain favorable tax consequences. This discussion comment focuses on several fundamental issues that confront researchers examining the backdating scandal and other related decisions. Specifically, we discuss the decision models for executives engaged in backdating and the potential role of social networks among directors, selection considerations, institutional voting behavior, and how backdated options can be replicated with existing equity instruments.